Impact of Coastal Reclamation on Environmental Sustainability and Tourism-Based Economy on the North Coast of Java - Turisno, Bambang Eko; Dew, I Gusti Ayu Gangga Santi (International Journal of Criminology and Sociology, 2021)
Coastal reclamation has been increasingly growing in Indonesia is done by multiplying natural resources and economy in coastal management for the welfare of the surrounding community. The research objective is to determine the potential of coastal reclamation land in Coastal residents that is sustainable and to reconstruct a just marine environment reclamation policy. This research can be broadly grouped into the realm of the socio-legal approach. The results of the research showed that the potential for marine reclamation on the north coast of Jawa for business development and tourism areas for the welfare of the surrounding community. Since 2014, the authority of the sea and the coast has become the authority of the provincial government. The authority and supervision of the regional government are reduced, considered detrimental for the life of the coastal community which is the majority of fishermen. Hence, the policy reconstruction of marine environment reclamation is carried out by reconstructing the value of policies in the form of making policies that genuinely involve community and reconstructing the laws and regulations that are still in force.